E-Government Institutional Capacity in Provincial Governments of West-Java and East-Java - Yogi Suwarno; Nila Kurnia Wati (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to analyse the institutional capacity of provincial governments of West-Java and East-Java on e-government in Indonesia in order to provide lessons learned for the government in developing e-government institutions. It uses a qualitative method with a case study approach to explore the implementation of e-government in local governments. This research focuses on five dimensions of the action environment, public sector institutions, task networks, organizations and human resources, and the Chief Information Officer (CIO). The results showed that, the action environment dimension of each region has different social and economic profiles so that the literacy level of the population in responding to e-government also varies. For the second and third dimensions, unlike the East Java province, the West Java province has specific rules and procedures as well as clear standards and planning related to e-government. Yet, the West Java province has not determined particular regulation on task and duty of its Office of Communication and Information. The aspect of the human resource dimension shows that the professional ICT group has not yet been fulfilled and there are still many positions related to IT are occupied by those who have no IT background. With regard to CIOs, only West Java province that has specific rules regarding CIOs.